Solving a bi-objective cell formation problem with stochastic production quantities by a two-phase fuzzy linear programming approach - Rabbani, Masoud; Jolai, Fariborz; Manavizadeh, Neda; Radmehr, Farzad; Javadi, Babak (International journal of advanced manufacturing technology, 2012)
We propose a bi-objective cell formation problem with demand of products expressed in a number of probabilistic scenarios. To deal with the uncertain demand of products, a framework of two-stage stochastic programming model is presented. The proposed model considers minimizing the sum of the miscellaneous costs (machine constant cost, expected machine variable cost, cell fixed-charge cost, and expected intercell movement cost) and expected total cell loading variation. Because of conflicting objectives, we develop a two-phase fuzzy linear programming approach for solving bi-objective cell formation problem. To show the effectiveness of the proposed approach, numerical examples are solved and the results are compared with the two existing approaches in the literature. The computational results show that the proposed fuzzy method achieves lower objective functions as well as higher satisfaction degrees.